Faktor-Faktor Terkait Pengambilan Keputusan Orang Tua Dalam Pemberian Vaksin Virus Human Papilloma Pada Anak - Winancy, Winancy; Salsabila, Nadifah; Sukamti, Sri (Poltekkes Kemenkes Jakarta III, 2024)
Cervical cancer has been the second most common cancer in women and at high-risk to death. It is commonly caused by HumanPapillomaVirus (HPV) so that it is considered making effective use of HPV vaccine to prevent this disease. This study is aimed to investigate factors associated with parents' decision-making to get HPV vaccine for children at the State Primary Schools located in the Community Health Center working area of Binong, Tangerang, in 2024. An analytical survey with cross-sectional design was employed in this quantitative study. 87 people out of the whole population of female students at SDN Binong I-VI were selected as samples of the study. Samples were collected by means of Cluster Random Sampling and data gathered was analyzed by using a Chi-Square test. The study found that a substantial majority of parents administer the HPV vaccine to their children (78.2%). In bivariate analysis, no statistically significant relationship was observed between education level and the decision to vaccinate children against HPV (p = 0.637). However, significant associations were identified between knowledge level (p = 0.000), motivation (p = 0.004), family support (p = 0.000), exposure to information (p = 0.000), and the decision to vaccinate children against HPV.